Protection of intellectual property in the world trading system: the TRIPS agreement and developing countries - Klaus Liebig (Deutsches Institut für Entwicklungspolitik (DIE), 2001)
The Agreement on Trade Related Aspects of Intellectual Property Rights (TRIPS) is one of the aspects of the world trading system on which the views of the industrialized and developing countries are sharply divided. While the industrialized countries celebrate the Agreement as a breakthrough in the global protection of intellectual property, the developing countries fear that rising prices of knowledge-intensive products and impeded access to know-how will delay their technological catching-up process.Intellectual property rights are an important means of promoting technological progress because they give inventors monopoly rights in their innovations for a limited period. This has the disadvantage of preventing the socially desirable earliest possible dissemination of knowledge.The TRIPS Agreement is leading to the international approximation of legislation on the protection of intellectual property at a relatively high level and to a significant increase in protection in most developing countries. The less developed countries will suffer welfare losses; more advanced developing countries may also benefit from stronger intellectual property rights because of increasing technology transfer and domestic innovation.Neither the historical experience of today's industrialized countries nor economic theory endorse every aspect of the TRIPS Agreement. In patent law in particular there is room for development-friendly reforms. The flexibility allowed by the Agreement should be retained and, where appropriate, widened. At all events, the industrialized countries must refrain from using bilateral pressure to induce developing countries to afford even greater protection to intellectual property than that required by the TRIPS Agreement.The TRIPS Agreement raises major problems in developing countries when little or no advantage is taken of existing flexibility. Many developing countries need help with the incorporation of the requirements of the Agreement into national legislation with appropriate account taken of their economic and social needs.Apart from participating in the debates in the World Trade Organization, industrialized countries should increase their efforts to make relevant know-how and technology available to developing countries: targeted incentives may promote the transfer of technology to developing countries; public research in areas of relevance to developing countries should again be stepped up; public research institutions should be granted special authorization to use patented products and processes.
Keywords: 330